Evaluation of Three Newly Developed Enzyme-Linked Immunosorbent Assays and Two Agglutination Tests for Detecting Salmonella enterica subsp. enterica Serovar Dublin Infections in Dairy Cattle - Veling, J. (American Society for Microbiology, 2000)
In this study test characteristics of three newly developed enzyme-linked immunosorbent assays (ELISAs) for Salmonella enterica subsp. enterica serovar Dublin were evaluated and compared with two agglutination tests. The ELISAs involved were an indirect ELISA with serovar Dublin lipopolysaccharide (LPS ELISA), an indirect ELISA with serovar Dublin flagellar antigen (GP ELISA), and a double-antibody sandwich blocking ELISA that uses monoclonal antibodies against S. enterica subsp. enterica serovar Enteritidis flagellin (GM-DAS ELISA). The agglutination tests involved were two routine serum agglutination tests with either somatic (O) or flagellar (H) antigen. Diagnostic specificity of the three ELISAs was determined using 840 serum samples from seven dairy herds without any history of serovar Dublin infection. Cutoff values at a titer of 100, 100, and 10, respectively, for the LPS ELISA, GP ELISA, and GM-DAS blocking ELISA resulted in a specificity of 99.3, 100, and 100%, respectively. Using these cutoff values the LPS ELISA, GP ELISA, and GM-DAS ELISA were able to detect, respectively, 30, 46, and 38% of 50 fecal culture-positive animals from 13 herds with a recent serovar Dublin infection. With the same cutoff values, active carriers (n = 18) were detected for 94.4% with the LPS ELISA and for 100% with the GP and GM-DAS ELISAs. Kappa values determined on the results of all tests from 8 of the 13 serovar Dublin-infected herds and the 7 control herds demonstrated a good correlation between the results of all ELISAs and the H-agglutination test. The results of the O-agglutination test failed to correlate with those of the other tests. Using a set of sera from 170 aborting cows (with 25 abortions due to serovar Dublin), test results of the ELISAs and the H-agglutination test were comparable. The H-agglutination test may be used successfully for single sample testing, especially to diagnose abortion due to serovar Dublin. It is concluded that the ELISAs are useful diagnostic tools in serovar Dublin control programs and that they are preferred to agglutination tests for reasons of automation and costs.